The potential of satellite-based data to detect weather extremes and crop yield variation for hedging agricultural weather risks in Central Asia and Mongolia: Three essays - Sarvarbek Eltazarov (Universitäts- und Landesbibliothek Sachsen-Anhalt, 2023)
The increasing availability of open-source and high-quality satellite data has facilitated market developments in the index insurance sector. However, the suitability of various satellite products for detecting weather extremes and crop yield variations across world regions must be thoroughly assessed. Therefore, this dissertation investigates the feasibility and performance of various satellite and reanalysis-based weather and vegetation data to design index insurance products for agricultural producers. According to the results, the studied satellite-based data could serve as a good source to establish and implement index insurance products in the region. However, careful assessment and selection of index, temporal aggregation, and land use/cover classification remain essential. – – Die zunehmende Verfügbarkeit offener und qualitativ hochwertiger Satellitendaten hat die Marktentwicklung im Bereich der Indexversicherung erleichtert. Allerdings muss die Eignung verschiedener Satellitenprodukte für die Erkennung von Wetterextremen und Ernteertragsschwankungen in verschiedenen Regionen der Welt gründlich geprüft werden. Ziel der Dissertation ist es daher, die Machbarkeit und Leistungsfähigkeit verschiedener Wetter- und Vegetationsdaten auf der Grundlage von Satelliten und Reanalyse zu untersuchen, um Indexversicherungsprodukte für landwirtschaftliche Erzeuger zu entwickeln. Die Ergebnisse zeigen, dass die untersuchten satellitengestützten Wetter- und Vegetationsdaten eine gute Quelle für die Einführung und Umsetzung von Indexversicherungsprodukten in der Region darstellen. Eine sorgfältige Bewertung und Auswahl des Indexes, der zeitlichen Aggregation und der Klassifizierung der Landnutzung/Bodenbedeckung ist jedoch weiterhin unerlässlich.
Keywords: 330